A genetic linkage map of sweetpotato [Ipomoea batatas (L.) Lam.] based on AFLP markers - Kriegner, A.; Cervantes, J.C.; Burg, K.; Mwanga, R.O.M.; Zhang, D.P. (Springer, 2003)
Amplified Fragment Length Polymorphism (AFLP) based genetic linkage maps were developed for hexaploid sweetpotato (Ipomoea batatas (L.) Lam., 2n = 6x = 90) using a segregating population derived from a biparental cross between the cultivars 'Tanzania' and 'Bikilamaliya'. A total of 632 ('Tanzania') and 435 ('Bikilamaliya') AFLPs could be ordered in 90 and 80 linkage groups, respectively. Total map lengths were 3655.6 cM and 3011.5 cM, respectively, with an average distance of 5.8 cM between adjacent markers. The genetic linkage analysis was performed in two steps. First a framework map was elaborated from the single dose markers. Interspersed duplex and double-simplex markers were used to detect homologous groups within and corresponding linkage groups among the parental maps. The type of polyploidy (autopolyploidy vs. allopolyploidy) was examined using the ratio of linkage in coupling phase to linkage in repulsion phase and the ratio of non-simplex to simplex markers. Our data support the predominance of polysomic inheritance with some degree of preferential pairing.